2021
DOI: 10.1111/jfpp.16045
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification through oil addition on the properties of yellowfin tuna ( Thunnus albacares ) paste

Abstract: In this study, the effects of different amounts of oil addition on the properties of tuna paste were investigated. The whiteness gradually improved with the oil addition. The water holding capacity increased from 0.28 without oil addition to a peak of 0.47 with 15% oil addition before decreasing to 0.21% at 35% oil addition. Changes in properties were measured by a rotational rheometer. Changes in protein secondary structure were evaluated by Fourier transform infrared spectroscopy. The particle size measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…76 The increase in the transition peak may be due to the presence of fat and oil incorporated in the batter, which might have improved the transfer temperature of actin. 77 The results of the present study concur with those of Keenan et al, 78 who explained that the polysaccharides containing more hydroxyl groups can replace hydrogen bond interactions as water is removed from the batter matrix, which is of benefit in preventing the denaturation of the native protein. They further observed that the water-binding effect of the inulin increased the thermal temperature in the second peak in the meat matrix, which might have limited the hydration of starch (added in the formulation) and changed their gelatinization temperature.…”
Section: Thermal Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…76 The increase in the transition peak may be due to the presence of fat and oil incorporated in the batter, which might have improved the transfer temperature of actin. 77 The results of the present study concur with those of Keenan et al, 78 who explained that the polysaccharides containing more hydroxyl groups can replace hydrogen bond interactions as water is removed from the batter matrix, which is of benefit in preventing the denaturation of the native protein. They further observed that the water-binding effect of the inulin increased the thermal temperature in the second peak in the meat matrix, which might have limited the hydration of starch (added in the formulation) and changed their gelatinization temperature.…”
Section: Thermal Stabilitysupporting
confidence: 92%
“…The melting temperatures of peak 2 of the T‐1, T‐2, T‐3, and T‐4 sausages increased as the inulin content increased from 1–4%, which might be due to the increased initiation of hydrogen bonds and hydrophobic interactions in the batter that require higher temperatures to disrupt the ordered structure 76 . The increase in the transition peak may be due to the presence of fat and oil incorporated in the batter, which might have improved the transfer temperature of actin 77 . The results of the present study concur with those of Keenan et al ., 78 who explained that the polysaccharides containing more hydroxyl groups can replace hydrogen bond interactions as water is removed from the batter matrix, which is of benefit in preventing the denaturation of the native protein.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al. (2021) found that the addition of < 20% sunflower seed oil improved the thermal stability of actin through lipid–protein interactions. However, excessive addition of oil destabilized the emulsification system.…”
Section: Benefitsmentioning
confidence: 99%